Gα12 and Gα13: Versatility in Physiology and Pathology - Guo, Paipai; Tai, Yu; Wang, Manman; Sun, Hanfei; Zhang, Lingling; Wei, Wei; Xiang, Yang K.; Wang, Qingtong (Frontiers in Cell and Developmental Biology, 2022)
G protein-coupled receptors (GPCRs), as the largest family of receptors in the human body, are involved in the pathological mechanisms of many diseases. Heterotrimeric G proteins represent the main molecular switch and receive cell surface signals from activated GPCRs. Growing evidence suggests that Gα12 subfamily (Gα12/13)-mediated signaling plays a crucial role in cellular function and various pathological processes. The current research on the physiological and pathological function of Gα12/13 is constantly expanding, Changes in the expression levels of Gα12/13 have been found in a wide range of human diseases. However, the mechanistic research on Gα12/13 is scattered. This review briefly describes the structural sequences of the Gα12/13 isoforms and introduces the coupling of GPCRs and non-GPCRs to Gα12/13. The effects of Gα12/13 on RhoA and other signaling pathways and their roles in cell proliferation, migration, and immune cell function, are discussed. Finally, we focus on the pathological impacts of Gα12/13 in cancer, inflammation, metabolic diseases, fibrotic diseases, and circulatory disorders are brought to focus.